(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study aimed to develop a straightforward, precise, and accurate method for the analysis of Teneligliptin, Metformin, and Pioglitazone in pharmaceutical dosage forms. Method: The separation was achieved using a Waters UPLC system with a Welch C18 column (150×4.6mm, 2 µm) and a mobile phase consisting of Methanol: ACN: Phosphate Buffer pH 2.5 (70:05:25), adjusted with orthophosphoric acid. The flow rate was set at 0.5 mL/min, and detection was performed at 238 nm using a photodiode array detector. Result: The complete validation of the analytical method was conducted following ICH guidelines. Recovery studies were performed at concentrations ranging from 50% to 150%, yielding results between 98% and 102%. The linearity ranges were determined as 0.08-4 µg/mL for Teneligliptin, 2-100 µg/mL for Metformin, and 0.06-3 µg/mL for Pioglitazone, with linear regression curves showing R2 values of 0.999. The method exhibited limits of detection (LOD) and quantification (LOQ) of 0.04 and 0.12 µg/mL for Teneligliptin, 0.32 and 0.97 µg/mL for Metformin, and 0.19 and 0.58 µg/mL for Pioglitazone, respectively. Retention times were 3.00 min for Teneligliptin, 2.55 min for Metformin, and 3.92 min for Pioglitazone. Intra-day and inter-day relative standard deviations were below 2%, confirming the method’s precision. Ruggedness and robustness evaluations, conducted according to ICH guidelines, also demonstrated satisfactory results. Conclusion: The developed UPLC method is suitable for the simultaneous estimation of Teneligliptin, Metformin, and Pioglitazone in pharmaceutical dosage forms, offering a reliable approach for routine analysis.